Extraction, Evaluation and Formulation of Herbal V -Wash from Hibiscus Rosa Sinensis - D. Rasal, Ashwini; Varpe, Anushka S.; Gawali, Sakshi A.; K. Benke, Sonali; P. Sonawane, Jayashree; D. Pawar, Tejaswini; Phadtare, Dipti G.; Nikam, Preetam L. (Journal of Neonatal Surgery, 2025)
The main aim of the present study is to formulate an effective herbal V Wash of white hibiscus flowers, which can produce a better antibacterial activity against various bacterial infections. Hibiscus rosa sinensis, a plant from the Malvaceae family, is widely distributed in tropical and subtropical climates, with around 40 species found in India. Known for its diverse medicinal properties, hibiscus is used to treat various ailments such as amoebic colitis, abdominal pain, cold, cough, diarrhea, headache, and ulcers. It contains bioactive compounds exhibiting anti-inflammatory, antibacterial, antifertility, antifungal, and antihypertensive activities. The plant's leaves, flowers, roots, and bark are integral in traditional medicine across several cultures. Hibiscus has applications in teas, tinctures, cosmetics, essential oils, and the food and pharmaceutical industries. The therapeutic value of hibiscus extends globally, from anti-diarrheal treatments in Japan to diuretic uses in Egypt, establishing it as a key component in herbal remedies. It was found that F1 batch is pale yellowish in colour and smooth texture with pleasant odour with pH of 3.98, viscosity is 1042 m.Pa.s, foaming height is 10 mm and no irritation found on human skin. The antibacterial activity determines by Disk Diffusion method. F1 batch shows more activity against E. coli, Bacillus and it was inactive against Pseudomonas aeurogenosa and Staphylococcus aureus.